Adverse Childhood Experiences and Justice-Involved Youth: The Effect of Trauma and Programming on Different Recidivistic Outcomes - Kowalski, Melissa A. (Youth violence and juvenile justice, 2019)
Studies have demonstrated that adverse childhood experiences (ACEs) are prevalent in justice-involved youth and related to recidivism. However, the effect of programming on reducing reoffending for youth with a trauma history is not well researched. This study aims to examine the prevalence of ACEs across different subsets of justice-involved youth, as well as the impact of family-based programming and aggression replacement training (ART) for youth exposed to ACEs. Presence of ACEs among 50,862 in Washington State is examined via multiple statistical tests. Results indicate that ACEs are prevalent in this sample, with higher ACE scores being associated with a greater risk of reoffending for different types of recidivism. Both family-based programming and ART had an impact on recidivism for males, while only completion of ART resulted in a decreased odds of reoffending for females. However, an intervention between programming and ACEs was nonsignificant, indicating that these particular interventions are not more beneficial for youth exposed to trauma than they are for the general justice-involved youth population. Findings outline the need to give ACEs serious consideration in the juvenile justice system, as these trauma experiences can inform case management and programming.